Blood clams community (Anadara granoasa) in The Eastern Coastal Waters of Banyuasin Regency South Sumatera - Rini Setianingsih; Hilda Zulkifli; Zazili Hanafiah (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: This research aimed to study existence of blood clams population and the environmental factors that affect them. This research was conducted in the coastal waters of Banyuasin in February 2015. The blood clamp sample was collected using Ekman Grab at low tide. From the observation in the research site, the highest population density was 60 ind/m2 with clay substrate texture, while the lowest density was 20 ind/m2 on the dusty clay substrate. Blood clams population was not found on the sand substrate texture station. Morphometric data showed that the blood clam population in the research site, including the medium category with b < 3 growth pattern (allometric negative). The results of PCA analysis proved that the habitat texture and sediment organic habitats were dominant factors besides the chemical physics environmental factors of the waters (temperature, salinity, pH).Keywords: Blood clams, density, morphometric, PCA Abstrak (Indonesian): Penelitian ini bertujuan untuk mempelajari keberadaan populasi kerang-darah dan faktor lingkungan yang mempengaruhinya. Penelitian ini dilakukan di perairan pesisir Banyuasin pada bulan Februari 2015. Sampel kerang-darah diambil dengan mengunakan Ekman Grab pada saat air surut. Dari hasil pengamatan pada lokasi penelitian, kepadatan populasi kerang-darah tertinggi adalah 60 ind/m2 dengan tekstur substrat lempung, sedangkan kepadatan terendah adalah 20 ind/m2 pada substrat lempung berdebu. Populasi kerang-darah tidak ditemukan pada stasiun dengan tekstur substrat pasir. Data morfometrik menunjukan bahwa populasi kerang-darah di lokasi penelitian termasuk kategori sedang dengan pola pertumbuhan b < 3 (allometrik negatif). Hasil analisis PCA membuktikan bahwa tekstur habitat dan bahan organik sedimen merupakan faktor dominan disamping faktor lingkungan fisika kimia perairan (suhu, salinitas, pH).Kata kunci: Kerang-darah, kepadatan, morfometrik, PCA